Hungarian Secondary School Students’ Extramural English Interests: The Development and Validation of a Questionnaire - Fajt, Balázs (Working Papers in Language Pedagogy, 2021)
Leisure time (or extramural) English activities have been an important resource in foreign language teaching and learning for decades. They may provide a plethora of EFL input, thus contributing to learners’ second language development even from an early age. The incorporation of extramural English activities into EFL lessons still remains rare, focusing only on mainly songs and short videos from YouTube. Despite this, an array of different extramural English activities is available, which could and should be exploited in EFL lessons in order to support second language acquisition. In the Hungarian context, little research investigates the potential impact of extramural English activities on the foreign language learning process, let alone the different individual learner differences. The aim of the present paper is to introduce a pilot study reporting on the development and validation process of a research instrument. The main aim of the study is to obtain insights into Hungarian secondary school students’ extramural English interests and individual learner differences, namely motivation, anxiety, willingness to communicate and additional variables affecting these learner differences. The preliminary results of the study show that Hungarian EFL learners engage in several extramural English activities on a regular basis and participants seem to show a relatively positive attitude to the use of English language subtitles. Furthermore, certain extramural English activities seem to have a positive impact on extramural motivated language use. It is hoped that the findings of this study will contribute to a better understanding of Hungarian secondary school EFL students’ engagement habits in extramural English activities, which may prove useful for EFL teachers planning to incorporate their students’ extramural interests into their EFL lessons.